IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP): DALAM PEMBELAJARAN SENI MUSIK DI SMA CITISCHOOL SEMARANG (Harmonia: Journal of Arts Research and Education, 2009)
The aim of this research are to explain implementation of KTSP in music learning in SMACitischool Semarang consists of planning, implementation of learning, and learning evaluation. Thisresearch uses qualitative-descriptive approach. Techniques of data collection aree literature studies,interview, observation, and documentation. In analyzing data, the researcher use descriptive andinteractive analysis from Milles, which consists of data collection, data reduction, data presentation,and conclusion. Research result shows that music learning in SMA Citischool Semarang 2008/2009are appropriate with KTSP : (a) learning plan have been conducted by teachers by making: developsyllabus and evaluation, annual program, semester program, and plan of learning, (b) learningprocess is appropriate with KTSP (competence standard) consists of appreciation and creation, butthe quality of learning is needed to be increased, and (c) evaluation is still influenced by curriculumevaluation before that consist of three aspects: cognitive, psychomotor, and affective aspects.Suggestion in this research: quality of teachers’ administration should be increased, optimizelearning process, and learning evaluation should be appropriate with appreciation and creationaspects in activities.